The Effect of Employability on Generation Z Job Search Intention through Self-Efficacy with Self-Consciousness as Moderating Variable - Tiarapuspa Tiarapuspa; Islanova Selvia Rahmadianti; Wahyuningsih Wahyuningsih; Retno Sari Murtningsih; Santika Bani Rahmatullah; Rimajon Sotlikova (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Amid increasing labor market competition and rapid technological change, understanding the psychological factors influencing young job seekers has become increasingly important. The study addresses inconsistencies in prior findings on employability and self-efficacy, as well as limited evidence on the moderating mechanism of self-consciousness in the Indonesian context. This study examines the influence of self-perceived employability on job search intention among Generation Z in Jakarta, considering the mediating role of job search self-efficacy and the moderating role of self-consciousness. A quantitative approach was employed using purposive sampling, involving 197 Generation Z respondents across six municipalities in Jakarta. Data were collected through an online questionnaire and analyzed using structural equation modeling to test direct and mediating relationships, and regression analysis to examine moderation effects. The results indicate that self-perceived employability positively influences job search self-efficacy and job search intention, while job search self-efficacy significantly predicts job search intention. Further analysis confirms that job search self-efficacy partially mediates the employability-intention relationship, and self-consciousness strengthens the effect of self-efficacy on job search intention. These findings highlight the importance of psychological resources in shaping job search behavior among Generation Z and provide empirical insights for career development and recruitment strategies.